Análisis e Interpretación a los Estados Financieros de la Empresa Eléctrica Regional del Sur S.A. EERSSA de la ciudad de Loja, períodos 2022-2023. - Rodríguez Cabrera, María José (2025)
This Curricular Integration Work, entitled “Analysis and Interpretation of the Financial Statements of the Regional Electric Company of the South S.A. (ERSSA) of the city of Loja, 2022-2023 periods”, was developed with the objective of evaluating the financial and economic situation of the entity through financial analysis techniques and methods. Through vertical and horizontal analysis, a concrete vision of the financial structure and variations between both periods was obtained, allowing the identification of areas for improvement and strengthening. The study of financial indicators made it possible to examine key aspects such as liquidity, solvency, management and profitability, providing an integral perspective of the company's performance. The methodology used had a mixed qualitative and quantitative approach, with an exploratory-descriptive and correlational design. For this purpose, scientific, deductive, inductive, analytical and synthetic methods were used, together with observation techniques and bibliographic compilation. The information management was carried out by means of mathematical and statistical tools and the use of the Excel program. The results showed that, in the 2022-2023 financial structure, the Non-Current Assets subgroup increased by $6,586,886.84, due to higher long-term obligations. The Current Liabilities subgroup showed an increase of $7,469,261.42 due to accounts payable related to energy purchases, while Equity remained constant in common and preferred shares, although Retained Earnings increased by $23,215,645.36. Regarding the economic structure, income increased by $5,608,004.60, mainly due to ordinary income. Costs and expenses increased by $23,350,866.93, mainly due to cost of sales. Although the financial indicators reflect stability, excess liquidity and delays in payment management were detected. Profitability was positive in both periods, but with a worrisome decrease in the second period. Finally, a financial report was prepared to facilitate decision-making aimed at improving and growing the company, thus contributing to its long- term continuity.